E-Magazine Development with Social Emotional Learning Approach on Colloid Material in Context of Local Wisdom - Syahmani, Syahmani; Iriani, Rilia; Riana, Suci; Bakti, Iriani (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2022)
The rapid development of education in the Industrial Revolution 4.0 in various sectors of life in science and technology is a source of its own challenges for a teacher in the learning process, especially for preparing the teaching materials. This study aims to develop an E-Magazine that is valid, practical, and effective. This study applied Research and Development method with the ADDIE model. The subjects for this research are 32 students of SMAN 9 Banjarmasin in the academic year of 2021/2022. The trial implementation consisted of individual, small group, and limited trials. Data collection techniques were validation sheets, readability and response questionnaires, and test and non-test assessments while the data analysis used descriptive analysis. The results showed that the validity of the e-magazine with an average score of 4.6 categories was very valid in terms of content, presentation, language, and media aspects. The effectiveness which was seen based on N-gain for students' conceptual understanding was 0.67 (moderate) and learning motivation was 0.45 (moderate). This study shows that the use of e-magazines with SEL approach on colloid material in context of local wisdom is effective, and can be used in chemistry learning. Implications of SEL can help the growth of problem solvers, and collaborative academics is positively synergized with SEL and local wisdom (CASEL-LW) so that students can understand and solve the problems better.